1987
DOI: 10.1111/j.1529-8817.1987.tb04208.x
|View full text |Cite
|
Sign up to set email alerts
|

INTRASPECIFIC VARIATION IN THE DINOFLAGELLATE PERIDINIUM VOLZIP1

Abstract: Clonal zsolates of Peridinium volzii Lemmermzn were analyzed morphologicall) and bzochemzcall) Morphologzcal obsertutzons at the light microscope lezlel shoul the clones to be diferent varzetzes a n d forms of the same speczes. Bzochemical analqsis bj enzjme electrophoresis and jloul cjtornetrzc deterrninatzon of nuclear D N A quantzttes zndicates that these zsolates ure geneticall) heterogeneous without an) clear correlatzon exzstzng between morphologzcal varzatzon and bzochemzcal zlarzatzon. Isozjme anal)sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Karenia brevis’ photoresponses are not distinguished by their origin relative to the Texas and Florida coasts. Previous studies have shown that phytoplankton species isolated from the same location were related to each other when compared with the same species from different geographic regions (Hayhome et al. 1987, Rynearson and Armbrust 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Karenia brevis’ photoresponses are not distinguished by their origin relative to the Texas and Florida coasts. Previous studies have shown that phytoplankton species isolated from the same location were related to each other when compared with the same species from different geographic regions (Hayhome et al. 1987, Rynearson and Armbrust 2004).…”
mentioning
confidence: 99%
“…1999) and Crypthecodinium cohnii Seligo (Beam and Himes 1982) showed genetic variation based on geographic origin. However, work with Peridinium showed genetic variation among isolates from the same geographic region (Hayhome et al. 1987).…”
mentioning
confidence: 99%
“…There is evidence of extensive genetic variation in all phytoplankton species examined and also that the pattern of inheritance of characters is complex (Gallagher 1998). A genetic regulation of physiological traits has been shown for example in diatoms (Murphy and Guillard 1976), although no clear correlation between morphological and biochemical variations has been observed in the dinoflagellate Peridinium volzii Lemmerman (Hayhome et al 1987). Laboratory experiments suggest that the size of microreticulate cysts may be predominantly a genetically determined character rather than being influenced by environmental parameters, because a relationship between cyst diameter (D) and individual cross parents was observed (Bolch and Reynolds 2002).…”
mentioning
confidence: 99%
“…For example, different in isozyme banding patterns in neretic, shelf and oceanic populations of Thalassiosira pseudonana prompted Murphy & Guillard (1976) and Brand et al (1981) initially to suggest that this species was composed of clinal populations but later detailed morphological investigations separated each ecological population into a different species (Hasle, 1978(Hasle, , 1983 for Thalassiosira guillardii, oceanica and pseudonana). There are many examples among the dinoflagellates where significant insights into species complexes have been made with isozymes that show in some areas populations are unique and in others they are not (Alexandrium tamarense/fundyense/catenella, Cembella & Taylor, 1986, Cembella et al, 1989Hayhome et al, 1989; Gambierdiscus toxicus Chinain et al, 1997 and Peridinium volzii, Hayhome et al, 1987). In most of these cases, the isozyme conclusions were supported by further studies with sequence analyses.…”
Section: Analysis Of Population Structure Using Molecular Markersmentioning
confidence: 96%